Factors Influencing Construction Labour Productivity: An Indian Case Study - Thomas, Anu V.; Sudhakumar , J. (Penerbit Universiti Sains Malaysia, 2014)
Construction productivity is of interest to researchers and practitioners because of its impact on the performance of construction projects. Despite various studies to identify factors influencing productivity in other countries, no study has addressed productivity issues in India. This paper reports the results of a questionnaire survey of project managers, site engineers, supervisors and craftsmen, in the state of Kerala in India, to identify the factors influencing construction labour productivity. The top five factors identified as having a significant impact on productivity: (1) timely availability of materials at the worksite, (2) delayed material delivery by the supplier, (3) strikes called by political parties or hartals, (4) frequent revisions of drawings/design, resulting in additional work/rework and (5) timely availability of drawings at the worksite. The findings provide a better understanding of the factors influencing productivity in the Indian context and will aid construction practitioners in making effective plans for productivity improvement.